Duck Hepatitis A Virus Type 1 Induces eIF2α Phosphorylation-Dependent Cellular Translation Shutoff via PERK/GCN2 - Liu, Yuanzhi; Cheng, Anchun; Wang, Mingshu; Mao, Sai; Ou, Xumin; Yang, Qiao; Wu, Ying; Gao, Qun; Liu, Mafeng; Zhang, Shaqiu; Huang, Juan; Jia, Renyong; et al. (Frontiers in Microbiology, 2021)
Duck hepatitis A virus type 1 (DHAV-1) is one of the most deadly pathogens that endanger the duck industry. Most viruses usually turn off host translation after infection to facilitate viral replication and translation. For the first time report to our knowledge, DHAV-1 can induce eIF2α phosphorylation and inhibit cellular translation in DEFs. Moreover, the activity of DHAV-1 in the cells caused obvious eIF2α phosphorylation, which has nothing to do with the viral protein. Subsequently, we screened two kinases (PERK and GCN2) that affect eIF2α phosphorylation through inhibitors and shRNA. Notably, the role of GCN2 in other picornaviruses has not been reported. In addition, when the phosphorylation of eIF2α induced by DHAV-1 is inhibited, the translation efficiency of DEFs restores to a normal level, indicating that DHAV-1 induced cellular translation shutoff is dependent on eIF2α phosphorylation.